Histone methylation mediates plasticity of human FOXP3+ regulatory T cells by modulating signature gene expressions. Issue 3 (March 2014) - He, Haiqi; Ni, Bing; Tian, Yi; Tian, Zhiqiang; Chen, Yanke; Liu, Zhengwen; Yang, Xiaomei; Lv, Yi; Zhang, Yong
Summary CD4+ FOXP3+ regulatory T (Treg) cells constitute a heterogeneous and plastic T‐cell lineage that plays a pivotal role in maintaining immune homeostasis and immune tolerance. However, the fate of human Treg cells after loss of FOXP3 expression and the epigenetic mechanisms contributing to such a phenotype switch remain to be fully elucidated. In the current study, we demonstrate that human CD4+ CD25high CD127low/− Treg cells convert to two subpopulations with distinctive FOXP3+ and FOXP3− phenotypes following in vitro culture with anti‐CD3/CD28 and interleukin‐2. Digital gene expression analysis showed that upon in vitro expansion, human Treg cells down‐regulated Treg cell signature genes, such as FOXP3, CTLA4, ICOS, IKZF2 and LRRC32, but up‐regulated a set of T helper lineage‐associated genes, especially T helper type 2 (Th2)‐associated, such as GATA3, GFI1 and IL13. Subsequent chromatin immunoprecipitation‐sequencing of these subpopulations yielded genome‐wide maps of their H3K4me3 and H3K27me3 profiles. Surprisingly, reprogramming of Treg cells was associated with differential histone modifications, as evidenced by decreased abundance of permissive H3K4me3 within the down‐regulated Treg cell signature genes, such as FOXP3, CTLA4 and LRRC32 loci, and increased abundance of H3K4me3 within the Th2‐associated genes, such as IL4 and IL5; however, the H3K27me3 modification profile was not significantly different between the two subpopulations. In conclusion, this study revealed that loss of FOXP3 expression from human Treg cells during in vitro expansion can induce reprogramming to a T helper cell phenotype with a gene expression signature dominated by Th2 lineage‐associated genes, and that this cell type conversion may be mediated by histone methylation events.